Occupational injury risk by sex in a manufacturing cohort. Issue 9 (12th June 2014) - Tessier-Sherman, Baylah; Cantley, Linda F; Galusha, Deron; Slade, Martin D; Taiwo, Oyebode A; Cullen, Mark R
Abstract : Objectives: This study expands previous research comparing injury risk for women and men in a cohort of 24 000 US aluminium manufacturing workers in 15 facilities from 2001 to 2010. Methods: We compared injury rates (all injury, first aid, medical treatment, restricted work and lost work time) by sex and by job and sex. Using a mixed effect modelling approach, we calculated ORs and 95% CIs adjusting for age, job tenure, ethnicity and year as fixed effects and person, job and plant as random effects. Additionally, we modelled the data stratified by plant type to examine potential differences in injury risk between smelter (generally recognised as more hazardous) and fabrication production environments. Results: Risk of injury was higher for women in four out of the five injury outcomes: all injuries combined (OR: 1.58, CI 1.48 to 1.67), injuries requiring first aid (OR: 1.61, CI 1.54 to 1.70), injuries requiring medical treatment (OR: 1.18, CI 1.03 to 1.36) and injuries requiring restricted work (OR: 1.65, CI 1.46 to 1.87). No difference in the risk of lost time injury by sex was found in this cohort. Analyses stratified by plant type showed similarly elevated injury risk for women, although the risk estimates were higher in smelters than fabrication plants. Conclusions: To our knowledge, this is the largest single-firm study examining injury risk by sex with sufficient data to appropriately adjust for job. We show a consistently higher injury risk for women compared with men in the smelting and fabrication environments.